‘Ship sail’: personal and professional experiences as leverage for learning - Kappert-White, Annette (2019)
The current transnational climate is likely to continue to generate institutional and classroom situations whereby diverse experiences, beliefs, traditions, languages, and identities become the norm. Unfortunately, previous migrants have had less than favorable educational experiences in Britain due to standardisation, stagnation, and discrimination. This thesis uses life-world analytical autoethnography, research-based literature, and a bricolage of metaphors, stories, proverbs, and visuals, to explore ways in which historical and cultural experiences influence educational attainment. Whilst not entirely new, findings confirm that a reciprocal relationship exists between the professional, academic and educational attainment of Black migrant educators and their Black migrant students. It reiterates that the legacy of slavery is entrenched in education, society and family lives and is culpable for the negative educational achievement of Caribbean migrants in Britain and that narratives are capable of transferring stereotypical diaspora subject positions. However, the findings also confirm that when educators, which I use synonymously with teacher throughout, use and explore their personal and professional experiences, they are more likely to encourage and use their student’s experiences to inform the curriculum; inevitably creating a more inclusive educational environment as a leverage for learning, and this can help to eliminate the perpetuating educational disparities for BME educators and students.